IIUM Fertility Centre: the outcome of a year in-progress - Zainuddin, Ahmad Murad; Abdul Wahab, Azantee Yazmie; Ramli, Roszaman; M. Y., Hayati; Md. Ariffin, Norsina; K., Siti (Obstetrical & Gynaecological society of malaysia, 2010)
Objective : To analyze the ART outcome and factors associated with successful ART treatment for infertile couples in a newly set up IIUM fertility centre. Method : An observational prospective study conducted at IIUM fertility centre, Kuantan from 15th June until 31st Dec 2009. Outcome measures include clinical pregnancy rate, ongoing pregnancy rate, take home baby rate and complications rate. Result : Fifty-five first cycles of IVF/ICSI were studied. Mean embryos per transfer was 2.1±0.8 4 patients were pregnant (23.5%) from a single embryo transfer (SET). Clinical pregnancy rate was 30.9% (17/55). Ongoing pregnancy rate was 23.6% (13/55) and take home pregnancy rate was 21.8% (12/55). There was only one twin pregnancy. 9 patients (16.4%) had OHSS where 77.8% were mild and 22.2% were moderate. Conclusion : Take home baby rate at IIUM FC is comparable to most establish ART centres in Malaysia considering that this is only the first year of operation.